The impact of IT tools on students’ anxiety and learning outcomes in online education during force majeure - Amanova, A.; Dzhumazhanova, G.; Abdiraimova, E.; Sarmurzin, Ye.; Kazhimova, K. (Cogent Education, 2025)
Amidst the force majeure, the paper addresses the significant role of information technology in higher and postgraduate education, focusing on its impact on online learning and on students’ anxiety. The study conducted at Shakarim State University in Semey, Kazakhstan, used an experimental design, and the primary data collection method was a survey. A survey involving 240 students across various disciplines, averaging 20 years of age. The control group was studied according to the traditional scheme using basic online resources, while the experimental group used an interactive approach involving IT. Findings reveal a strong digital technology proficiency among respondents (78%), with preferences split between online video conferencing (39%) and recorded videos (45%). Despite a preference for classroom-based learning by some (45%), the majority found online courses effective (68%), highlighting the value of interactive forms (70%). The study demonstrates an average increase in preand post-training scores, indicating heightened student motivation through information technology (73.5–79.23). This underscores the efficacy of IT-based curricula in enhancing learning outcomes and student engagement. This finding suggests that the use of the experimental methodology contributed to a reduction in students’ anxiety.
Keywords: Education policy; force majeure; higher education pedagogy; information technology; innovations in education